Study of clay soils of Rio Grande do Sul - Goedert, Wenceslau J. (Pesquisa Agropecuaria Brasileira, 2014)
In collaboration with soil survey work in Rio Grande do Sul, a mineralogical study was made of clays in 26 units of souls already mapped. Most of them were situated in the plateau region of Rio Grande do Sul. Differential thermal analysis was used as the main method of study along with the use of X-ray and chemical data. The author has verified a great variation among the souls studied and has concluded by putting in groups of five classes the soils which are more or less homogeneous as to the quality of clay fraction.